Bistatic ISAR sparse aperture maneuvering target translational compensation imaging algorithm - Zhu, H. S.; Hu, W. H.; Guo, B. F.; Zhu, X. X.; Xue, D. F.; Zhu, C. A. (Společnost pro radioelektronické inženýrství, 2022)
For bistatic inverse synthetic aperture radar (Bi-ISAR), the non-uniform motion state of maneuvering target and the time-varying bistatic angle make the traditional imaging method of moving target face the problem of translation compensation, and the traditional translation compensation method is not suitable for the return wave in the case of sparse aperture. In this paper, a compensation imaging method combining two-dimension joint linearized Bregman iteration and image contrast search is proposed. The translation compensation problem can be transformed into two-dimension joint compressed sensing sparse reconstruction and moving target motion parameter estimation. The proposed algorithm makes use of the gain of echo two-dimension compression, greatly improves the accuracy of translation compensation and the quality of target image and has strong robustness to noise. The processing results of simulation data verify the effectiveness and superiority of the algorithm.
Keywords: Bistatic-ISAR; maneuvering target; sparse aperture; translational compensation